The Effects of Different Concentrations of Ethyl Alcohol as Drying Agent on Pit and Fissure Sealant Treatment. - Tamasas, Basma. (2017)
Abstract: Objective: Moisture contamination is considered one of the major causes for pit and fissure sealant failure. Post etchant drying agent has been proposed for use in dentistry to improve the retention of the sealant by evaporating the residual moisture. Therefore, the purpose of this in vitro study is to evaluate the microleakage of sealant placed after the application of ethyl alcohol (50% once, 99% once and 99% twice), as a post etchant drying agent. The effect of salivary contamination on microleakage will also be evaluated. Materials and Methods: Sixty four human molar teeth were randomly divided into eight groups of eight each. The treatment groups were defined by the combination of different drying agents (no drying agent, 50% ethyl alcohol once, 99% ethyl alcohol once and 99% ethyl alcohol twice) and salivary contamination condition (contaminated, not-contaminated). All teeth were sealed with Ultraseal XT Plus sealant. The teeth were thermocycled (2500 cycles at 5°C-55°C) and were then immersed in 50% silver nitrate. Mikroleakage was examined. Statistical analysis was done using one way ANOVA and independent sample t- test. Results: Sealant placed on teeth after the utilization of 50% ethyl alcohol showed significantly less microleakage than the other tested two drying agents and the control group (P < 0.001). Saliva contamination did significantly increase the microleakage. (P=0.001). Conclusions: Under the conditions used in this in-vitro study, the use of 50% ethyl alcohol as post etchant drying agent, under both contaminated and non-contaminated conditions, significantly reduced sealant microleakage.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Pediatric Dentistry.; Advisors: Gerard Kugel, and Masly Harsono.; Committee: Cheen Loo, and Matthew Finkelman.; Keyword: Dentistry.